2021
DOI: 10.1051/0004-6361/202141027
|View full text |Cite
|
Sign up to set email alerts
|

Chromospheric heating and generation of plasma outflows by impulsively generated two-fluid magnetoacoustic waves

Abstract: Context. The origin of the heating of the solar atmosphere is still an unsolved problem. As the photosphere and chromosphere radiate more energy than the solar corona it is challenging but important to reveal all the mechanisms that contribute to plasma heating there. Ion-neutral collisions could play an important role. Aims. Impulsively generated two-fluid magnetoacoustic waves are investigated in the partially ionized solar chromosphere and the associated heating and plasma outflows are studied, which higher… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 63 publications
1
18
0
Order By: Relevance
“…The authors concluded that ambipolar diffusion has the potential to efficiently heat the chromosphere. Additionally, Kuźma et al (2019), Niedziela et al (2021), andPelekhata et al (2021) showed that in the regime of two-fluid, respectively monochromatic acoustic, impulsively generated magneto-acoustic and Alfvén waves are likely to effectively heat the chromosphere. Moreover, Srivastava et al (2018) proposed that the smallscale, two-fluid penumbral jets that are omnipresent in active regions, possess sufficient energy to heat the solar corona.…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that ambipolar diffusion has the potential to efficiently heat the chromosphere. Additionally, Kuźma et al (2019), Niedziela et al (2021), andPelekhata et al (2021) showed that in the regime of two-fluid, respectively monochromatic acoustic, impulsively generated magneto-acoustic and Alfvén waves are likely to effectively heat the chromosphere. Moreover, Srivastava et al (2018) proposed that the smallscale, two-fluid penumbral jets that are omnipresent in active regions, possess sufficient energy to heat the solar corona.…”
Section: Introductionmentioning
confidence: 99%
“…It was specified that the maximum heating occurs for a pulse launched from the middle of the photosphere, mainly from y ≈ 0.3 Mm, and with the maximum pulse amplitude A = 10 km • s −1 . In the parallel research performed by Niedziela et al (2021), the effect of magnetoacoustic waves was studied in a similar framework, to show that these waves can also increase the chromospheric temperature and induce plasma outflows. In particular, Niedziela et al (2021) found that the heating rate grows with the initial pulse amplitude and with its width.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of Alfvén (Pelekhata et al 2021) and magnetoacoustic (Niedziela et al 2021) waves, heating of the chromosphere took place due to ion-neutral collisions. Both studies were performed using two-fluid and magnetohydrostatic equilibrium models.…”
Section: Introductionmentioning
confidence: 99%
“…Several methods have been introduced in the literature to derive the collisional terms at the kinetic level. In the classical multifluid approaches considered for solar atmospheric conditions (see Leake et al 2012;Alvarez Laguna et al 2016;Ni & Lukin 2018;Popescu Braileanu et al 2019;Ni et al 2020;Wójcik et al 2020;Niedziela et al 2021;Pelekhata et al 2021), a simplification of the transport coefficients is usually considered. Indeed, the cross sections do not depend on the local thermodynamic condition of the plasma and are sometimes assumed to be constant.…”
Section: Introductionmentioning
confidence: 99%
“…However, this approach is valid only for the multicomponent model developed by Graille et al (2009). These calculations have not been performed yet in the context of multifluid magnetohydrodynamics (MHD) models (see Khomenko et al 2014aKhomenko et al , 2014bAlvarez Laguna et al 2016;González-Morales et al 2018;Ni & Lukin 2018;Martinez-Sykora et al 2019;Popescu Braileanu et al 2019;Ni et al 2020;Wójcik et al 2020;Niedziela et al 2021;Pelekhata et al 2021) or single-fluid MHD models with an ambipolar diffusion coefficient that requires the calculation of collisional frequencies between ions and neutrals (see .…”
Section: Introductionmentioning
confidence: 99%